Dragnet-Controls and Government Ideology - Niklas Potrafke (Defence and Peace Economics, 2020)
In many European countries established leftwing and rightwing parties have been threatened by policy convergence and, in turn, new populist parties that offer more polarized platforms. I investigate whether government ideology influences dragnet-controls – controls of persons conducted by the police without having any suspicion that the controlled person committed a crime. They took effect after the Schengen Agreement in 1995. I propose dragnet-controls to be a prime example of ideology-induced policies implemented by established parties. Dragnet-controls confine citizens' liberties, but may help to detect criminals. Using data from the 16 German states over the period 1995–2017, I show that rightwing governments have been active in implementing dragnet-controls and leftwing governments have denied dragnet-controls since the mid 1990s. When evaluating how government/party ideology influences individual policies, previous econometric studies ignored initiatives in parliament. My study also considers initiatives in parliament. I conjecture that, since 2015, the rightwing CDU has used initiatives to introduce/extend dragnet-controls to also deal with the upcoming threat of rightwing populism. Future research should examine policy-differences between the established parties regarding more fine-grained policy measures also in other European countries.
Keywords: D72; F22; P16; 330; Dragnet-controls; government ideology; established parties; populism; Schengen Agreement; European countries